INTEGRATING ENVIRONMENTAL ISSUES INTO DEVELOPMENT PLANNING OF DINH VU ECONOMIC ZONE, HAI PHONG - Lan, Tran Dinh; Hens, Luc (Vietnam Journal of Marine Science and Technology, 2006)
INTEGRATING ENVIRONMENTAL ISSUES INTO DEVELOPMENT PLANNING OF DINH VU ECONOMIC ZONE, HAI PHONG